AB0806 Rituximab in clinical practice for the treatment of interstitial lung disease refractory to cyclophosphamide in patients with diffuse systemic sclerosis. (23rd January 2014) - Castellví, I.; Simeon, C.P.; Sarmiento, M.; Guillen, A.; Diaz-Torné, C.; Geli, C.; Casademont, J.; Fonollosa, V.; de Llobet, J.M.
Abstract : Background: Systemic sclerosis or scleroderma (SSc) is a connective tissue disease which frequently presents lung affectation, being the principal cause of death in these patients. Currently, only cyclophosphamide (CyC) has shown efficiency to treat this complication. However, this efficiency is modest and not kept through the time. Several medicines have been tested for the treatment of this complication with controversial results. Rituximab (RTX) seems to show improvement in patients with SSc and Interstitial Lung Disease (ILD) refractory to others treatments, but there are not pivotal assays in this regard and the experience is limited. Objectives: To study the evolution of Pulmonary Function Test (PFT) in patients with SSc affected by ILD refractory to usual treatment and have made at least one cycle of Rituximab. Methods: Multicenter observational prospective study in patients with ILD-SSc was performed. These patients had one cycle of two Rituximab infusions for ILD and previously had realized CyC, azathioprine or mycophenolic acid with treatment failure. We evaluated the following data: gender, age, onset age of Raynaud's phenomenon, age at diagnosis of SSc, age at diagnosis of ILD, ILD type, total dose of CYC, use of concomitants steroids, and other immunosuppressive agents. PFT outcome after each therapy and after 4 months of treatment with RTX was included. Results: We collected the data of four patients who realized one complete cycle of treatment with RTX. Patients were women and presented diffuse cutaneous shape with antitopoisomerase I antibodies. The radiologic affectation was Non-Specific Interstitial Pneumonia (NSIP) in all cases. Patient's characteristics are showed in table 1 . The patient who presented the best response to RTX (Patient 4) had the highest dose of CyC accumulated previously. As a whole, patients presented a worsening of the predicted value of FVC and DLCO after treatment with CyC. Four months later of RTX infusion, we did not observe any worsening in the values of FVC beside of a trend to improve the values of DLCO. The best response in concern to respiratory function parameters was not related with taking concomitant or accumulated dose of other drugs different to CYC. Conclusions: Rituximab could be an alternative to the treatment and stabilization for interstitial lung disease in patients with SSc, however experience remains limited. Disclosure of Interest: None Declared